Ball convergence of Potra-Ptak-type method with optimal fourth order of convergence - Ioannis K. Argyros; Santhosh George (Journal of Numerical Analysis and Approximation Theory, 2021)
We present a local convergence analysis Potra-Ptak-type method with optimal fourth order of convergence in order to approximate a solution of a nonlinear equation. In earlier studies such as [1], [5]-[28] hypotheses up to the fourth derivative are used.